Pengembangan Mobile Learning dengan Pendekatan Saintifik untuk Meningkatkan Kemandirian dan Hasil Belajar IPS di Kelas IV SD - Septi Sakiyah; Mustaji Mustaji; M. Turhan Yani (University of Bengkulu, 2022)
The goal of this study is to develop m-learning with a Scientific Approach to Improve Independence and Social Studies Learning Outcomes for Grade IV Elementary School. This study uses the DDD-E model by Ivers & Barron. The subjects of the research were fourth grade students of SDN Pucang 1 Sidoarjo which consisted of 35 students. Data collection techniques in the form of documentation, validation, observation, questionnaires, and tests. The results of the research include: (1) M-learning based on its appearance gets an average score of 3.9, while based on the material it gets an average score of 3.37; (2) The results of the implementation of lesson plans and student’s responses to the use of m-learning were 97.72% with positive response criteria; (3) The analysis results of the independence of students show the results of t-statistics 11,689 > t-table = 2,042, therefore a significant difference between and ; (4) Student learning outcomes show an increase. This study develops the concept of making contextual m-learning and it’s prioritizes the role of students to be independent and active during learning activities.